Revitalization of Organization and Business Determination of BUMDes Cibadak Mandiri of Cibadak Village, Ciampea District, Bogor Regency - Mokhamad Syaefudin Andrianto; Rindang Matoati; Wita Juwita Ermawati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
BUMDes Cibadak Mandiri has stopped operating, so to revive it, it must be replaced by new management. The new management seeks a partner to restore and run the business. The "Dosen IPB Mengabdi" program in BUMDes Cibadak Mandiri aims to assist management in analyzing and evaluating previous management problems, determining business priorities, and motivating new management. The method used in analyzing the problem was a fishbone diagram with a participatory approach and used the brainstorming approach to determine priority business. Management, business unit leaders, and local participants attended the activity. The six main issues found were a need for more capability of human resources, capital, business partner responsibilities, unstructured organization/management, nonperforming loan, and lack of market understanding. Several alternatives were proposed by participants, such as gathering/workshops, training, looking for committed people, investors, and open recruiting volunteers. At the same time, the business priorities that should be carried out are karst mountain tourism, distribution and management of clean water (PAM), and bottled drinking water (AMDK). The methods were conducted to raise awareness of the new board and the role of related stakeholders, especially agreements in describing problems, alternative solutions, and choices of BUMDes business priorities. These processes give valuable insight into the current state of management to reactivate of BUMDes and alternatives action to tackle this situation